Digital Parenting: Optimalisasi Peran Orang Tua dalam Dunia Pendidikan - Ririen, Deci; Erny, Erny; Nurjayanti, Nurjayanti; Sahriyal, Sahriyal; Daryanes, Febblina (ABDIMASY: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Parents play an important role in family education by providing care, affection and nurturing to children. In today's digital era, uncontrolled or inappropriate use of digital technology can carry risks. Therefore, parents or guardians should guide and control their children's use of digital technology. The purpose of this service is to increase parents' understanding of how to care for children in the digital era and improve parents' skills in finding information about digital parenting. The methods used include observation, discussion, coordination, presentation and evaluation. The results of this service activity can increase parents' knowledge about parenting and matters related to digital parenting based on an average pretest result of 52.8 points and an average posttest result of 75 points.